2021
DOI: 10.1016/j.jtos.2021.03.010
|View full text |Cite
|
Sign up to set email alerts
|

A single cell atlas of human cornea that defines its development, limbal progenitor cells and their interactions with the immune cells

Abstract: Purpose Single cell (sc) analyses of key embryonic, fetal and adult stages were performed to generate a comprehensive single cell atlas of all the corneal and adjacent conjunctival cell types from development to adulthood. Methods Four human adult and seventeen embryonic and fetal corneas from 10 to 21 post conception week (PCW) specimens were dissociated to single cells and subjected to scRNA- and/or ATAC-Seq using the 10x Genomics platform. These were embedded using U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
139
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(172 citation statements)
references
References 80 publications
(98 reference statements)
18
139
4
Order By: Relevance
“…The data generated can serve as a reference cell atlas with a major impact in the further improvement and development of cell replacement therapies or regenerative medicine approaches for treating corneal blindness. This research further complements scRNAseq analysis of the developing human cornea 42 and of the human corneal limbus 43 , 44 .
Figure 7 scRNAseq data analysis identified nine epithelial, four stromal and two endothelial corneal cell clusters.
…”
Section: Discussionmentioning
confidence: 63%
“…The data generated can serve as a reference cell atlas with a major impact in the further improvement and development of cell replacement therapies or regenerative medicine approaches for treating corneal blindness. This research further complements scRNAseq analysis of the developing human cornea 42 and of the human corneal limbus 43 , 44 .
Figure 7 scRNAseq data analysis identified nine epithelial, four stromal and two endothelial corneal cell clusters.
…”
Section: Discussionmentioning
confidence: 63%
“…A recent study used single cell RNA sequencing (scRNA-seq) to characterize cell types in the normal human cornea and conjunctiva [ 48 ]. Table 6 lists the twenty gene expression clusters identified in that study, showing the differential expression patterns of their signature genes in pterygium and pinguecula.…”
Section: Resultsmentioning
confidence: 99%
“…The global expression profile does not give information about which cell type(s) is expressing the differentially expressed gene. This challenge was addressed by utilizing cell-type signatures recently identified by scRNA-seq [ 48 , 49 ]. Based on this analysis, we concluded that most of the previously identified epithelial and stromal cell types were present in our specimens.…”
Section: Discussionmentioning
confidence: 99%
“… 37 Nevertheless, Col8 is also expressed in the central corneal stroma, 38 and Col8A2 by CSK. 39 We previously demonstrated, that Col8A2 expression is higher in CSK than in SF, and can be used to differentiate between the two. 17 …”
Section: Discussionmentioning
confidence: 97%